DYNAMICA OFACCMULATION OF DRYMATTER GRAIN SOFT WINTER WHEAT - Герман, М. М.; Міщенко, О. В. (Scientific Progress & Innovations, 2014)
The results of the studies found the best stage of ripeness soft winter wheat to produce high-quality seed. Determined that the principal amount of protein and gluten in grains synthesized by the middle of the milk, the next phase of ripening grain continues their accumulation in sufficiently moist years before full maturity, in the dry - the middle of ripeness of grain, regardless of its predecessor, background fertilizer and seed rates soft winter wheat seeds. Found that in dry warm weather and lack of rain during the development and ripening of grain daily gain mass of 1000 grains is much larger than in years with high rainfall.